Kegagalan Konsolidasi dan Politik Program: Dinamika Kekalahan Har–Guntur dalam Pilkada Kota Jambi 2024 - Irgi Ahmad Maulana Ibrahim; Ian Pasaribu; Galank Pratama; Nasuhaidi (Indonesian Democracy Research Center, 2026)
This study aims to explain the electoral defeat of the Har–Guntur pair in the 2024 Jambi City local election by emphasizing the interaction between internal candidate weaknesses and the strategic advantages of their opponents. Departing from the phenomenon of high political visibility that was not fully matched by electoral participation, as well as the limited availability of candidate alternatives, this research employs a qualitative approach through the analysis of survey data, media coverage, and campaign dynamics. The findings reveal that the defeat of Har–Guntur was not caused by a single factor, but rather by an accumulation of weaknesses, including poor consolidation of the campaign team, suboptimal performance of the supporting party machinery, and political communication strategies that failed to resonate with voters’ needs. In contrast, the Maulana–Diza pair effectively leveraged their strategic advantages by offering concrete programs, strengthening a people-oriented personal image, and utilizing communication channels more effectively. A significant gap in electability had already emerged prior to election day, indicating a systematically constructed political dominance. These findings underline that in the context of local politics, electoral victory is not solely determined by structural party support, but also by a candidate’s ability to integrate political consolidation, effective communication, and relevant programmatic offerings. This study contributes to the literature on voter behavior and local electoral competition by demonstrating that electoral defeat is the result of a complex interaction of multiple reinforcing factors.